2023
DOI: 10.3390/nu15020433
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diet Influences Human Milk Protein Concentration and Adipose Tissue Marker

Abstract: (1) Background: Adequate protein intake plays an essential role in growth and neurodevelopment, especially in preterm infants. We investigated the effects of maternal diet and body mass index (BMI) on human milk (HM) composition. (2) Methods: HM samples were obtained from 136 lactating mothers (BMI: 18.0–36.7 kg/m2), of which 93% gave birth to preterm infants. Macronutrient content in HM was measured by mid-infrared transmission spectroscopy. Leptin and adiponectin were analyzed using appropriate ELISAs. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Dietary protein intake impacts the protein content in breast milk [21][22][23]. Binder et al [7] reported that maternal diet is a major determinant of the quality of breast milk. Protein intake by the newborn is directly related to neurodevelopment [24], especially lactoferrin [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary protein intake impacts the protein content in breast milk [21][22][23]. Binder et al [7] reported that maternal diet is a major determinant of the quality of breast milk. Protein intake by the newborn is directly related to neurodevelopment [24], especially lactoferrin [25].…”
Section: Discussionmentioning
confidence: 99%
“…The composition of breast milk is not easily affected by race [6], while maternal diet is a major determinant of the quality of breast milk [7]. Nevertheless, due to different diets and physical conditions, the content, composition, and active constituents of fat in breast milk can be slightly different [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, fat and carbohydrate concentrations were not evaluated in this study. Third, this was a cross-sectional study, and we did not collect information about several factors reported to influence protein, sIgA, and lactoferrin levels in human milk, including maternal diet, body mass index, circadian rhythm, methods of milk expression, and the volume of milk expressed [ 36 , 38 , 49 , 50 , 51 , 52 ]. It will be necessary to investigate and standardize the effects of these factors on DHM composition in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal diet is known to impact several HM micronutrients (eg, vitamin A, vitamin B 6 , vitamin B 12 , folate, iodine, and selenium), as well as fatty acids, whereas the relationship between diet and other macronutrients in HM is less clear. 37,80,81 A 2016 systematic review found that 17 of 36 included publications focused on the fatty acid composition of maternal HM. 82 However, only three studies included the same exposure and outcome variables (milk DHA and maternal fish consumption), and the results were variable.…”
Section: Maternal Dietmentioning
confidence: 99%